Synthesis and Characterization of A Slowly-Released Polycarboxylate Superplasticizer with High Slump Retention. Issue 1 (November 2020) - Dang, Wei; Chen, Xiaobin; Xiong, Qiumin; Guo, Xiujuan; Xu, Han; Li, Guangzhou; Guan, Jican; Huang, Xiaohu
Abstract: A slowly-released polycarboxylate superplasticizer with high slump retention was obtained at room temperature by using Isoamyl enol polyoxyethylene ether (TPEG), 2-hydroxyethyl acrylate (HEA), acrylic acid(AA), and acrylamide (AM) as the main raw material, and using hydrogen peroxide (H2 O2 ) as initiator and mercaptoacetic acid as the chain transfer agent. The effect of initiator dosage, chain transfer agent dosage and acrylamide dosage on the performance of the product were investigated. The results showed that under the optimum polymerization conditions of the slowly-released polycarboxylate superplasticizer with high slump retention, the dosage of initiator, chain transfer agent and acrylamide was 0.3%, 0.25% and 0.9% based on the mass of the macromonomer, respectively. The molecular weight distribution under the optimum synthesis conditions was determined by gel permeation chromatography (GPC) and the structure of the polymer was characterized by spectroscopy (FTIR). Compared with commercial similar produces and other synthesized slowly-released polycarboxylate superplasticizer, the test results showed that the developed superplasticizer had an excellent slump retention ability.